Sharia as Revelation with Sharia as the Result of Thoughts: Comparative Analysis of Vertical, Horizontal and Diagonal - Ni'matul Maola (JURNAL PENDIDIKAN IPS, 2024)
This paper discusses the difference between sharia as revelation and sharia as a product / result of thought and the relevance between the two. The massive development of the times gave birth to Muslim groups that have different opinions in understanding sharia as revelation and sharia as the result of thought. Differences in understanding of both often lead to conflict and debate to fanaticism. The type of research in this article is library research using a normative approach and using comparative vertical, horizontal, and diagonal analysis. The results of this paper found that there are differences between sharia as revelation and sharia as a result of thought. Sharia as a revelation is in the form of the Qur'an and sunnah while sharia as a result of thought is the result of ijtihad of the mujtahids in interpreting the texts of the Qur'an and sunnah in the form of fiqh, fatwa, and jurisprudence